Організація і нормування праці за принципами соціально-економічної безпеки на підприємствах харчової промисловості - Драган, Олена Іванівна; Бергер, Аліна Дмитрівна (My University, 2021)
У статті обґрунтовується актуальність дослідження організації і нормування праці з урахуванням принципів соціально-економічної безпеки. Соціально-економічна безпека підприємства на перше місце ставить всебічне врахування інтересів, потреб і захисту людини у сфері праці. Узагальнено класифікацію загроз техніко-технологічній безпеці підприємства з поділом на зовнішні та внутрішні. Розроблено сучасну структуру техніко-технологічної безпеки, за складовими, зокрема, стан та рівень техніко-технологічної бази підприємства, виробнича безпека, охорона праці, техніка безпека, система управління охороною здоров’я і безпекою праці. Проаналізовані негативні тенденції у розвитку організації і нормування праці підприємств харчової промисловості сьогодення. Запропоновані заходи щодо удосконалення організації і нормування праці на підприємствах харчової промисловості з урахуванням принципів соціально-економічної безпеки та міжнародного досвіду. The actuality of research’s improvement of organization and set of labour norms taking into account principles of socio-economic safety is established in the article. The increase of organization efficiency and set of labour norms of food industry enterprises, the estimation influences on the qualities of operating norms, that must take into account all factors and risks of food productions by the modern standards of personnel safety is proven in the article. Socio-economic safety of the enterprise respect the person’s interests, necessities and his/ her safety in the sphere of labour. The personnel as the basic value of the enterprise must work in safe normal terms and with the high labour productivity. The influence of socio-economic safety through the component of technical and economical safety on labour organization and its constituent of set of labour norms is offered in the article. The classification of threats of technological and technical safety of the enterprise with dividing them into external and internal is generalized. The modern structure of technical and technological safety by the constituents, in particular, the state and level of technical and technological base of the enterprise, productive safety, labour safety, technician safety protection, control system of health protection and labour safety is worked out. The best enterprises of food industry are certificated by the standards of ISO 9001 “System of management quality”, ISO 22000 “System of management safety of food products” and ISO 45001 “Control system of health protection and labour safety”, that fully answers the requirements of technical and technological safety, organization and set of labour norms. Especially popular distribution of introduction standard experience of ISO 45001 as the most modern world requirements to the health protection and labour safety in obedience to International Labour Organization. The negative tendencies in organization and set of labour norms of food industry enterprises of present time are analyzed. The events in relation to the improvement of organization and set of labour norms on the food industry enterprises, taking into account the principles of socio-economic safety and international experience in accordance with standards, positions and rules of International Labour Organization are offered.
Keywords: соціально-економічна безпека; організація праці; нормування праці; техніко-технологічна безпека; стандарти; безпека праці; social and economic safety; labor organization; labor rationing; technical and technological safety; standards; labor safety; кафедра економіки праці та менеджменту; кафедра маркетингу